Mortality and Thrombosis in Injured Adults Receiving Tranexamic Acid in the Post-CRASH-2 Era - Simranjeet Benipal; John-Lloyd Santamarina; Linda Vo; Daniel K. Nishijima (Western Journal of Emergency Medicine, 2019)
Introduction: The CRASH-2 trial demonstrated that tranexamic acid (TXA) reduced mortality with no increase in adverse events in severely injured adults. TXA has since been widely used in injured adults worldwide. Our objective was to estimate mortality and adverse events in adults with trauma receiving TXA in studies published after the CRASH-2 trial. Methods: We systematically searched PubMed, Embase, MicroMedex, and ClinicalTrials.gov for studies that included injured adults who received TXA and reported mortality and/or adverse events. Two reviewers independently assessed study eligibility, abstracted data, and assessed the risk of bias. We conducted meta-analyses using random effects models to estimate the incidence of mortality at 28 or 30 days and in-hospital thrombotic events. Results: We included 19 studies and 13 studies in the systematic review and meta-analyses, respectively. The pooled incidence of mortality at 28 or 30 days (five studies, 1538 patients) was 10.1% (95% confidence interval [CI], 7.8–12.4%) (vs 14.5% [95% CI, 13.9–15.2%] in the CRASH-2 trial), and the pooled incidence of in-hospital thrombotic events (nine studies, 1656 patients) was 5.9% (95% CI, 3.3–8.5%) (vs 2.0% [95% CI, 1.8–2.3%] in the CRASH-2 trial). Conclusion: Compared to the CRASH-2 trial, adult trauma patients receiving TXA identified in our systematic review had a lower incidence of mortality at 28 or 30 days, but a higher incidence of in-hospital thrombotic events. Our findings neither support nor refute the findings of the CRASH-2 trial but suggest that incidence rates in adults with trauma in settings outside of the CRASH-2 trial may be different than those observed in the CRASH-2 trial.